Cost and Benefit Analysis of Desulfurization System in Power Plant - Zhang Caiqing; Liu Meilong (Universitas Ahmad Dahlan, 2014)
The economy of desulfurization system is of great significance for operation of desulfurization system and improving the environment quality in power plant. Based on the desulfurization power price policy, this paper analyzes the cost and benefit structure of the wet flue gas desulfurization system in Chinese power plant; that puts forward the calculation methods of total cost present value, total benefits present value and net present value during the life period of desulphurization system. Moreover using Cost-benefit sensitivity analysis to find out that there is sensitivity relationship between power generation hour and desulphurizer price. By applies these methods, the result shows that the economy of desulfurization system is better under the current designed scheme. But with the reduced power hour and risen price of limestone, the current desulfurization system power price policy of China cannot compensate the running cost of the desulfurization system in power plant rationally, and leads to lower economy of desulfurization system.